Understanding the regulatory and transcriptional complexity of the genome through structure - Mercer, Tim R.; Mattick, John S.

(untitled) (Genome Research, 2013)
An expansive functionality and complexity has been ascribed to the majority of the human genome that was unanticipated at the outset of the draft sequence and assembly a decade ago. We are now faced with the challenge of integrating and interpreting this complexity in order to achieve a coherent view of genome biology. We argue that the linear representation of the genome exacerbates this complexity and an understanding of its three-dimensional structure is central to interpreting the regulatory and transcriptional architecture of the genome. Chromatin conformation capture techniques and high-resolution microscopy have afforded an emergent global view of genome structure within the nucleus. Chromosomes fold into complex, territorialized three-dimensional domains in concert with specialized subnuclear bodies that harbor concentrations of transcription and splicing machinery. The signature of these folds is retained within the layered regulatory landscapes annotated by chromatin immunoprecipitation, and we propose that genome contacts are reflected in the organization and expression of interweaved networks of overlapping coding and noncoding transcripts. This pervasive impact of genome structure favors a preeminent role for the nucleoskeleton and RNA in regulating gene expression by organizing these folds and contacts. Accordingly, we propose that the local and global three-dimensional structure of the genome provides a consistent, integrated, and intuitive framework for interpreting and understanding the regulatory and transcriptional complexity of the human genome.